(untitled) (Journal of Oriental Studies, 2016)
This article is devoted to the theme of culinary codes in Kazakh and Chinese languages. Comparative analysis, as well as their classification are given here. Differences between figurative expressions in both languages on culinary topics give an idea about the distinctive features of each culture.